Moodle course in teaching English language for specific purposes for masters in mechanical engineering - Hanna M. Shalatska; Olena Yu. Zotova-Sadylo; Ivan O. Muzyka (Academy of Cognitive and Natural Sciences, 2020)
The central thesis of this paper is that e-learning courses can have a significant impact on English language for specific purposes (ESP) proficiency of mining mechanical engineering students. The purpose of this study is to assess the effectiveness of ESP Moodle-based course "English for Mining Mechanical Engineers" and to reveal the results of its experimental approbation. In order to identify the lectures' and learners' needs we have applied the survey research. The survey confirmed the greatest demand for Moodle courses that include all the elements of a coherent training manual to provide self-development of engineering students. The interview results contributed to design of author's ESP course syllabus. The importance and originality of this study are that to approbate the course materials' effectiveness two approaches have been adopted simultaneously. The first is blended learning method based on e-learning platform applied in the experimental group and the second one is classic in-class instructor-led studying used in a control group. Students' progress in ESP proficiency has been assessed using the cross assessment method. The experiment has validated the initial hypothesis that the special online courses focused on honing foreign language skills and integrated in the domain of specific professional knowledge have a beneficial effect on students' communicative competencies in general. There were identified the advantages of self-tuition based on Moodle platform. The Moodle course lets the teachers save considerable in-class time to focus more on communicative assignments. The findings of this study have a number of practical implications in ESP online courses development.